Information communications technology penetration and stock markets - growth nexus: from cross country panel evidence. (2018) - Pradhan, Rudra P.; Mallik, Girijasankar; Bagchi, Tapan P.; Sharma, Manoranjan
The study assesses the long run and causal relationship amongst three variables, namely, ICT penetration, stock markets development, and per capita economic growth in the emerging and growth-leading economies (EAGLEs) as evidenced between 1988 and 2012. Using panel cointegration technique, this study found that the variables under study are cointegrated and there exists a long run relationship among these variables. Furthermore, using vector error correction modelling (VECM) technique and Granger causality this study found that Granger causality exists among these variables both in the short run and in the long run although the exact nature of the results vary for the select ICT penetration indicators in use within the EAGLEs.